Multifunctional rhizobacteria: use in agriculture (Research, Society and Development, 2022)
The use of innovative and sustainable technologies that excel in the development of productive agricultural systems, such as multifunctional rhizobacteria, are essential to ensure food safety and quality. Therefore, this theoretical study, carried out through an exploratory bibliographic research and qualitative approach, aimed to bring information regarding multifunctional rhizobacteria, addressing the general aspects, main characteristics, some genera of agricultural importance, their main mechanisms of action and the importance of co-inoculation. Multifunctional rhizobacteria are rhizospheric, endophytic or symbiotic bacteria that can improve plant growth, enhancing productivity. The use of these bacteria in agricultural systems has proved to be an innovative and sustainable technology due to different mechanisms of action, which can be direct or indirect, to benefit plants and the environment. Multifunctional rhizobacteria promote plant growth and suppression of diseases and, therefore, make it possible to reduce the use of synthetic inputs such as fertilizers and pesticides. There are different genera of multifunctional rhizobacteria and they can show synergism and, therefore, greater efficiency using the co-inoculation technique. This technique consists of adding more than one recognized beneficial microorganism to plants, to maximize their contribution. Co-inoculation provides several benefits for the greater development of plants, such as the increase in the root system, which allows better uptake of fertilizers, favors the plant in situations of water deficiency and increases productivity. However, several challenges still need to be overcome, such as the selection of efficient strains for specific crops, compatibility with products used in seed treatment, and obtaining consistent agronomic results under field conditions. Therefore, studies in this direction are very important to increase knowledge about multifunctional rhizobacteria and contribute to making Mayan agricultural systems efficient and sustainable.